Analisis Kesulitan Belajar Siswa Dalam Mata Pelajaran Electrical Di SMK Penerbangan Nusantara Ketaping - Nurpahana .; Habibullah . (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
The Electrical subject plays an important role in equipping vocational high school (SMK) students with the fundamental electrical skills needed in the workforce. However, many students still face difficulties in understanding the subject matter, both in theory and practice. These difficulties are suspected to be caused by low learning motivation, limited facilities, less varied teaching methods, and suboptimal teacher-student interpersonal relationships. Based on these issues, this study aims to analyze the factors causing students‟ learning difficulties and to identify the level of learning difficulties in the Electrical subject at SMK Penerbangan Nusantara Ketaping.This research employed a descriptive quantitative method. Data collection was conducted through questionnaires distributed to 80 eleventh-grade students as a sample from a total population of 100 students. The research instrument was developed based on five main aspects: theoretical understanding, practical ability, learning motivation, school facilities, and teacher-student relations. The data were analyzed using descriptive statistical techniques to determine the percentages and levels of difficulty in each aspect. The results showed that students‟ learning difficulties in the Electrical subject were categorized as moderate to high. The most dominant contributing factors were limited practical facilities and low learning motivation. Additionally, many students experienced difficulties in understanding electrical components and their working principles. These findings indicate the need for improving the quality of learning through facility enhancement, more engaging teaching methods, and efforts to boost students‟ learning motivation to achieve better learning outcomes.